2021
DOI: 10.1038/s41598-020-79345-4
|View full text |Cite
|
Sign up to set email alerts
|

Circulating adiponectin and leptin and risk of overall and aggressive prostate cancer: a systematic review and meta-analysis

Abstract: Obesity is associated with an increased risk of advanced, recurrent and fatal prostate cancer. Adipokines may mediate this relationship. We conducted a systematic review and meta-analysis of associations of leptin and adiponectin with overall and aggressive prostate cancer. Bibliographic databases were systematically searched up to 1st April 2017. Log Odds Ratios (ORs) per 2.5 unit increase in adiponectin or leptin levels were derived and pooled. All analyses were stratified by study type (cross-sectional/pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 70 publications
1
13
1
Order By: Relevance
“…It has been supposed that adipokines, such as leptin and adiponectin, may be the molecular mechanism behind the link between obesity and prostate cancer progression. However, Leptin was not associated with an increased risk of prostate cancer (odds ratio [OR] = 1.00) whereas evidence of a positive association with aggressive disease was observed (OR = 1.03) [14 ▪▪ ]. On the other hand, adiponectin resulted in a protective factor of overall prostate cancer risk (OR = 0.96) and aggressive disease (OR = 0.98) [14 ▪▪ ].…”
Section: Recent Findings On Obesity Metabolic Syndrome and Cancermentioning
confidence: 94%
See 1 more Smart Citation
“…It has been supposed that adipokines, such as leptin and adiponectin, may be the molecular mechanism behind the link between obesity and prostate cancer progression. However, Leptin was not associated with an increased risk of prostate cancer (odds ratio [OR] = 1.00) whereas evidence of a positive association with aggressive disease was observed (OR = 1.03) [14 ▪▪ ]. On the other hand, adiponectin resulted in a protective factor of overall prostate cancer risk (OR = 0.96) and aggressive disease (OR = 0.98) [14 ▪▪ ].…”
Section: Recent Findings On Obesity Metabolic Syndrome and Cancermentioning
confidence: 94%
“…However, Leptin was not associated with an increased risk of prostate cancer (odds ratio [OR] = 1.00) whereas evidence of a positive association with aggressive disease was observed (OR = 1.03) [14 ▪▪ ]. On the other hand, adiponectin resulted in a protective factor of overall prostate cancer risk (OR = 0.96) and aggressive disease (OR = 0.98) [14 ▪▪ ]. Besides adipokines, a major role in tumorigenesis is reserved for steroid hormones and insulin/insulin-like growth factor 1 (IGF1) pathways.…”
Section: Recent Findings On Obesity Metabolic Syndrome and Cancermentioning
confidence: 99%
“…Indeed, AT dysfunction, observed in conditions of chronic energy excess, MetS and obesity, further increases leptin production which in turn, due to its proinflammatory nature, augments cytokine production and T-cell proliferation, thereby amplifying AT inflammation [ 159 , 161 , 162 ]. Within the context of PCa, leptin was not consistently associated with overall PCa and there was weak evidence of a positive association between leptin and PCa aggressiveness [ 163 ]. Nevertheless, hyperleptinemia remains a preeminent feature of PCa and PCa tissues express higher levels of leptin and the leptin receptor in comparison to BPH and healthy prostates [ 164 ].…”
Section: Periprostatic Adipose Tissue Secretome and Prostate Cancer P...mentioning
confidence: 99%
“…Although the available literature concerning the associations between serum adiponectin levels and the various facets of carcinogenesis is quite conflicting, the most accredited hypothesis is that adiponectin exerts a protective role against the development and progression of PCa [ 163 , 197 , 198 , 199 ]. A meta-analysis concluded that the concentration of adiponectin in PCa patients was significantly lower than in control subjects [ 200 ].…”
Section: Periprostatic Adipose Tissue Secretome and Prostate Cancer P...mentioning
confidence: 99%
“…Clinical studies indicated a positive correlation between leptin:adiponectin ratio and increased risks for some cancers like ECa in post-menopausal women ( 72 ), BCa ( 73 ) and PCa ( 74 ). However, a metanalysis has then discussed leptin:adiponectin ratio and demonstrated no strong prognosis value for PCa ( 75 ).…”
Section: Cancer and Adipocyte Secretomementioning
confidence: 99%